Climate adaptation in cities: What trees are suitable for urban heat management? - Lanza, Kevin; Stone, Brian (Landscape and urban planning, 2016)
•We examine the effect of hardiness zone shifts on tree distribution in the US.•All Southeastern US MSAs in our study lost tree species over time.•Continuing the hardiness zone shift change pattern results in greater species loss.•Of the projected tree species lost, deciduous outnumbered coniferous 3 to 1. Vegetative enhancement in the form of tree planting has been found to be a highly effective strategy for cooling urban environments, yet as cities continue to warm, the suitability of urban environments for some tree species is changing with shifting hardiness zones. Trees are assigned to hardiness zones, which are based on the average annual minimum temperature that a species can thrive. In recent decades, human induced global warming has shifted the location of hardiness zones across the United States. Our study examines the historical range of ∼200 common US tree species and how climate change-induced shifts in hardiness zones are affecting historical tree ranges in 20 highly populated metropolitan statistical areas (MSAs) with high rates of urban heat island growth over time. MSAs are areas with at least one urban area of 50,000 or more people and adjoining territory that has a high degree of social and economic integration with the core. We found 6 of the 20 MSAs lost tree species, with the Atlanta (13.51%) and Washington DC (3.61%) MSAs suffering the greatest losses. If historical rates of hardiness zone migration continue, a simple projection exhibits >6% average tree species loss across all MSAs in the study. As hardiness zones continue to migrate northward with climate change, heat island mitigation and other environmental management strategies employing green infrastructure must identify tree species that are likely to remain well adapted to urban climates many years into the future.